1991
DOI: 10.1111/j.1530-0277.1991.tb05215.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Ethanol Exposure on Cardiac Receptor‐Adenylyl Cyclase Coupling: Studies in Cultured Embryonic Chick Myocytes and Ethanol Fed Rats

Abstract: Ethanol effects in the brain appear to be mediated at least in part by an alteration in receptor-effector coupling via guanine nucleotide-binding regulatory proteins (G proteins). To test the hypothesis that a similar pathway participates in the cardiotoxic effects of ethanol, we assessed the effects of chronic ethanol on two commonly used experimental models: embryonic chick myocytes in culture and ventricular myocardium from chronically fed rats. Ethanol had no effect on either the function or quantity of G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Treatment of primary hepatocyte cultures with ethanol over 2-4 days in culture results in increased responsiveness to receptor-stimulated cyclic AMP production (Table 1) [8]. A similar increase in glucagonand forskolin-stimulated cyclic AMP production in liver membranes isolated from rats fed ethanol for 8 weeks has been reported [7]. As adenosine, interacting with adenosine A2 receptors, has been found to mediate the decrease in cyclic AMP production observed in NG108-15 cells after chronic treatment with ethanol [4], we postulated that adenosine may also be involved in the effects of ethanol on cyclic AMP production in cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Treatment of primary hepatocyte cultures with ethanol over 2-4 days in culture results in increased responsiveness to receptor-stimulated cyclic AMP production (Table 1) [8]. A similar increase in glucagonand forskolin-stimulated cyclic AMP production in liver membranes isolated from rats fed ethanol for 8 weeks has been reported [7]. As adenosine, interacting with adenosine A2 receptors, has been found to mediate the decrease in cyclic AMP production observed in NG108-15 cells after chronic treatment with ethanol [4], we postulated that adenosine may also be involved in the effects of ethanol on cyclic AMP production in cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 57%
“…This desensitization has been observed after ethanol exposure of cultured NG108-15 neuroblastoma x glioma and S49 lymphoma cells [2,4], as well as in rat cortex after long-term ethanol consumption [3] and peripheral lymphocytes from chronic alcoholics [5,6]. In contrast, increased receptor-and forskolin-stimulated cyclic AMP production has been reported in rat liver membranes after chronic alcohol consumption [7]. Similarly, chronic exposure of primary cultures of rat hepatocytes to ethanol increases receptor-and forskolin-stimulated cyclic AMP levels [8].…”
Section: Introductionmentioning
confidence: 97%
“…In fact, when we studied the behavior of another receptor-mediated event in the present experimental model, we observed that ␤-adrenoceptor stimulation of adenylate cyclase activity increased in prostate after chronic ethanol intake. Similar protocols of ethanol feeding also resulted in disparities among tissues, for example, an increase in ␤-agonist-stimulated adenylate cyclase activity in rat myocardium [31] or in the cerebellar tissues, but not in hippocampus from ethanol-fed mice [32].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the investigation of the effects of ethanol upstream of the CP450Arom transcription found that acute and chronic exposure to ethanol concentrations above 0.5 % provides a greater stability to adenylyl cyclase (AC), blocks the Gαi function and promotes an irregular increase in cAMP production [ 54 , 57 59 ]. This increase in cAMP levels in turn promotes the transactivation of target genes for CREB, such as CP450Arom [ 53 ] and the mitogen agonist belonging to the endothelial growth factor family, Amphiregulin (Amph) [ 48 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%